Project Management of the Creation of an Online Platform for the Exchange and Sale of Used iItems “EcoChange Haven” - Zhang, Xinyang (Lesya Ukrainka Volyn National University, 2024)
The master’s thesis examines the project management of the creation of an online platform for the exchange and sale of second-hand items EcoChange Haven. In the context of the general growth of interest in electronic commerce and the development of the second-hand goods market, the research of this project is of practical importance. The first chapter explores theoretical and methodological aspects of project management in the field of e-commerce, including an overview of concepts and approaches to project management in the field of e-commerce, analysis of modern trends in the use of online platforms for the exchange and sale of secondhand goods, as well as project management methods in the e-commerce industry commerce and trade. The second chapter examines aspects related to concept development, technical analysis of the project, and budget development. Important aspects such as the development process and technology stack selection, design and user interface, testing and launch of the platform are covered. In the third section, management of the project schedule and team, risk management and evaluation of the effectiveness and prospects of expanding the online platform are considered. The work is based on the analysis of current sources and methods of project management and is aimed at developing an effective strategy for creating and managing an online platform for the exchange and sale of used things, which has significant potential for market implementation. The significance of projects lies in their ability to promote sustainable development and reduce environmental impact. They provide an opportunity for the efficient use of resources through the reuse and resale of used goods, reducing waste and fostering the development of a circular economy. Additionally, such platforms contribute to economic growth by providing new opportunities for small businesses and individual sellers, as well as increasing consumer awareness of environmental issues and solutions.
Keywords: project management; e-commerce; business strategies for the online market; project management methodology; project risk management